Emerging Role of Ultrasound in Dysphagia Assessment and Intervention: A Narrative Review - Hsiao, Ming-Yen; Wu, Chueh-Hung; Wang, Tyng-Guey (Frontiers in Rehabilitation Sciences, 2021)
Ultrasonography has gained increasing attention as a non-invasive and radiation-free instrument for assessment of swallowing function. In the past decades, an extensive repertoire of ultrasonographic techniques including B-mode dynamic scanning, pixel analysis, M-mode, Doppler, 3D reconstruction and sonoelastography has been applied in the evaluation of oropharyngeal structures and movement. Yet, a universal consensus on the examination protocols and clinical implications remains to be established. This review aims to provide a brief introduction of the application of ultrasound in dysphagia assessment and intervention, encompassing the ultrasonography of swallowing-related muscles, tongue movement and hyolaryngeal excursion, as well as ultrasound-guided interventions in the management of dysphagia. With its portability, ease of use and low cost, in addition to non-invasiveness, ultrasonography could compliment videofluoroscopic swallowing study as a first-line screening and follow-up tool for the evaluation of swallowing function, although further study is warranted to provide quantitative diagnostic and prognostic values. Finally, ultrasonography aids in the precisely targeted injection of botulinum toxin in patients exhibiting oropharyngeal muscle spasticity.